Exploring student's pattern generalisation strategy in solving prism sticker problem - Lisanul Uswah Sadieda; Kusaeri Kusaeri; Siti Lailiyah; Wachidatul Adaniyah (Universitas Islam Negeri (UIN) Mataram, 2018)
[English]: This research aimed to describe the stages through which eighth-grade students develop pattern generalizations when solving prism sticker problem and determine the type of strategy used. Prism sticker problem is a modified task from cube sticker problem that Lannin (2003) has used in developing student’s pattern generalization. Prism Sticker problem uses triangular prism-shaped media that will be affixed with color stickers. The subjects of the research were eighth-grade students of public junior high schools in Krian City, East Java, Indonesia. The results of this research show that the subjects can go through the four stages of the pattern generalization process, i.e., direct modeling, pattern identification, proof testing of the pattern, and determining the rule for a general case. The subjects can formulate the nth pattern by using algebraic symbols and explain it verbally. The results indicate that the subjects tend to use counting and explicit strategies to solve prism sticker problem. Keywords: Pattern generalization, Strategy, Prism sticker problem, Problem-solving [Bahasa]: Penelitian ini bertujuan untuk mendeskripsikan tahap-tahap yang dilalui siswa SMP dalam mengembangkan generalisasi pola saat menyelesaikan prism sticker problem dan menentukan jenis strategi yang digunakan. Prism sticker problem merupakan suatu tugas hasil modifikasi dari cube sticker problem yang telah digunakan Lannin (2003) dalam mengembangkan generalisasi pola siswa. Prism sticker problem menggunakan media berbentuk prisma segitiga yang akan ditempeli stiker warna. Subjek dalam penelitian ini adalah siswa kelas 8 SMPN 2 Krian. Hasil penelitian ini menunjukkan bahwa subjek mampu melalui keempat tahap proses generalisasi pola yaitu pemodelan langsung, identifikasi pola, pembuktian pola dan penentuan aturan untuk kasus yang lebih umum. Subjek mampu merumuskan pola ke-n dengan menggunakan simbol aljabar dan menjelaskannya secara verbal. Dalam penelitian ini, subjek cenderung menggunakan strategi counting dan explicit dalam menyelesaikan prism sticker problem. Kata Kunci: Pola generalisasi, Strategi, Prism sticker, Pemecahan masalah